Understanding the process of knowledge transfer to achieve successful technological innovation - Gilbert, Myrna (Technovation)
This paper is concerned with the ability of organizations to innovate and successfully achieve technological and organizational change. It recognizes the complexity of the issues that contribute to the management of such change the role of the learning organization. Through the use of organizational and technological literature it presents the development of a conceptual model for understanding the processes of knowledge transfer. The use of the model is demonstrated within a case study which explores the successful introduction of technology change into a division of a major bank. The study investigates in detail, through the reflections of individuals within the company, the activities and behaviours that have led to the successful introduction of technology change. The paper includes some of the findings and analysis of the study. The use of the model as a tool for understanding organizational processes is evaluated.